TikTok's Influence on Marriage and Relationship Attitudes among Young Adults in Urban Kampala - Petra Cherukut; Hakim Nkalubo; Augustine O. Ifelebuegu (PT Agung Media Publisher, 2025)
This study examines how TikTok content about marriage and relationships influences the perceptions of young adults in urban Kampala, Uganda. Drawing on Cultivation Theory, the research explores the ways social media narratives shape relational attitudes in a rapidly digitising society. A qualitative case study design was employed with forty purposively selected participants (20 men and 20 women, aged 18–35). Data were collected through semi-structured interviews and focus group discussions, and analysed thematically. The analysis revealed that TikTok communicates recurring messages highlighting open communication, shared responsibility, gender collaboration, and support for single parenthood. At the same time, the platform often presents glamorised and unrealistic portrayals of marriage and intimate life. Participants found these messages both empowering and problematic: they encouraged collaboration and offered practical advice, but also promoted unrealistic expectations, trend-driven pressures, and discouraging images of marital life. The findings suggest that TikTok functions as a dual-edged cultural tool. It provides valuable relational lessons while simultaneously glamorising and normalising idealised or dysfunctional dynamics. The study highlights the need for media literacy initiatives to enable young people in Uganda to critically evaluate digital ideals of relationships within their cultural context.